Characterization of the hass avocado productive chain: analysis and optimization strategies from the circular economy - Caballero Deza, Luis Carlos (2025)
The objective of the research was the characterization and analysis of the Hass avocado production chain in Peru, in order to identify strategies for its optimization based on the circular economy. A non-experimental and descriptive design methodology was used, validated by sector experts, which included the structural analysis of sectoral factors, the identification of critical variables and the formulation of strategic solutions through statistical modeling of structural equations using Python and R. The results highlight Hass avocado production and agronomic management as key variables, and producers, suppliers and society as predominant actors in the dynamics of the sector. It was evident that the generation of byproducts within the Hass avocado production process represents the most viable proposal. This theoretical approach allowed us to understand production dynamics and address the technical, economic and environmental challenges in the value chain, in addition to envisioning new lines of research for efficient methodologies to produce by-products and the introduction of new agricultural products.